The Effects of Mindfulness and Self-Compassion on Improving the Capacity to Adapt to Stress Situations in Elderly People Living in the Community. Issue 2 (14th March 2016) - Perez-Blasco, Josefa; Sales, Alicia; Meléndez, Juan C; Mayordomo, Teresa
ABSTRACT: Objectives : This study aimed to show the effectiveness of mindfulness and self-compassion therapy in improving coping ability and adaptation to stressful situations in the elderly.Methods : Forty-five elderly non-institutionalized adults were randomized to either treatment or a treatment waiting list. A pre- and post-treatment assessment was performed, consisting of the Brief Resilient Coping Scale (BRCS), Depression Anxiety Stress Scales (DASS), and Coping Strategies Questionnaire. The program was developed over 10 sessions lasting 120 minutes each.Results : Analysis of variance for repeated measures showed significant differences in the time-group interaction for the treatment's effectiveness in improving resilience, positive reappraisal and avoidance strategies, and decreasing anxiety, problem-solving coping, negative self-focus, overt emotional expression and religion.Conclusions : The mindfulness and self-compassion program is useful for improving resilience and coping strategies and reducing anxiety and stress levels in the elderly.